Мовознавчі роздуми в листах професора Юрія Олексійовича Жлуктенка - Зорівчак, Р.П. (Мовознавство, 2015)
У цій публікації подано добірку листів професора Юрія Олексійовича Жлуктенка до перекладознавця та германіста Роксолани Петрівни Зорівчак, яка в 60-80-ті роки працювала над кандидатською та докторською дисертаціями з перекладознавства. Листи присвячено дисертаційним проблемам, передусім у галузі фразеології та перекладознавства. У них читач може знайти також чимало цікавої інформації про суспільне життя того періоду. A collection of letters by Professoe Yuriy Zhluktenko to Roksolana Zorivchak is being presented. Professor was the most brilliant scholar in Germanic Studies in Ukraine in the second half of the 20th c. whose aim was to develop and promote Ukrainian Studies. He pioneered in researching the American and Canadian territorial dialects of the Ukrainian language. Professor was the first to contrast the Ukrainian, German and English languages on lexical, grammatical and stylistic levels in the light of current scholarly paradigms. The researcher elaborated the methods of teaching Ukrainian to students of English-language linguistic background. He has also made a substantial contribution to Ukrainian lexicography. He essentially developed the theory, methods and linguostylistics of translation studies analysis, elaborated the principles of researching the history of Ukrainian literary translation. To enrich the Ukrainian translated literature he mastered rarely used languages of limited diffusion—Frisian and Flemish to make translations from those languages. The letters discuss the problems connected with Candidate and Doctoral theses written by Zorivchak, mainly concerning phraseology and translation studies. But they also elucidate social problems of that period (the 60-80-ies of the previous century).